A Correlation Analysis of Geomagnetic Field Characteristics in Geomagnetic Perceiving Navigation - Li, Hong; Qu, Junsuo; Jiang, Xiangkui; Niu, Yun (Frontiers in Neurorobotics, 2021)
It is well-known that the geomagnetic fields have multiple components or parameters, and the parameters are related to each other. This paper mainly discusses the correlation of geomagnetic field parameters for the geomagnetic navigation technology. In this paper, the correlation coefficient similarity is adopted to calculate between the geomagnetic parameters, at the same time, the search algorithm (Hex-path algorithm) is used to verify the correlation analysis results. The results show that the same convergent state for the approximate correlation coefficient. In other words, the approximate correlation coefficient between the geomagnetic parameters can be regarded as one class.